РОЗВИТОК СІЛЬСЬКО-МІСЬКИХ АГЛОМЕРАЦІЙНИХ УТВОРЕНЬ НА ЗАСАДАХ ІНКЛЮЗИВНОСТІ: УКРАЇНСЬКИЙ ТА МІЖНАРОДНИЙ КОНТЕКСТ - Лопатинський, Юрій (My University, 2024)
У статті сформульовано та реалізовано завдання, пов’язані з аналітикою вітчизняного та зарубіжного контексту розвитку сільсько-міських агломераційних утворень на інклюзивних засадах. У процесі дослідження було визначено сутність агломерацій та виявлено спільні та відмінні риси класичних (міських) агломерацій та сільсько-міських агломераційних утворень. Увагу приділено характеристиці передумов та чинників формування сільсько-міських агломерацій, витоки яких беруть свій початок від здійснення в Україні реформи децентралізації публічної влади та управління. Доведено, що формування у просторових межах об’єднаних територіальних громад і укрупнених районів зі «змішаним» складом населення, наявними різноманітними ресурсами та функціями, спільними інтересами сільського та міського населення, згуртованого навколо розв’язання невідкладних соціально-економічних проблем, пов’язаних з нерівністю та бідністю, надало поштовх для включення сільсько-міської спільноти у процес створення інклюзії добробуту. За результатами дослідження зроблено висновки та окреслено напрями подальших наукових розвідок за цією проблематикою.
DEVELOPMENT OF RURAL-URBAN AGGLOMERATION FORMATIONS ON THE BASIS OF INCLUSIVENESS: UKRAINIAN AND INTERNATIONAL CONTEXT
At the current stage of the development of globalization, which is characterized by increasing contradictions between the development of urbanization and ruralization both in developed countries and in developing countries, the role of agglomeration formations in solving socio-economic, ecological and political problems is growing. In Ukraine, the growth of the role of agglomerations in the development of various spheres of social life due to the consequences of the reform of decentralization of public power and management, the conditions of war. Given this, the chosen research topic has significant scientific relevance and practical significance. The purpose of the study is to analyze the domestic and international context of the development of rural-urban agglomeration formations on the basis of inclusiveness. For her implementation, the following tasks were formulated: to find out the essence, common and distinctive features of urban and rural-urban agglomerations; to to determine the factors of formation of rural-urban agglomeration formations in Ukraine and in foreign countries; to characterize the specifics of the development of Ukrainian rural-urban agglomerations on the basis of inclusiveness in comparison with their foreign counterparts. In the process of research, the essence of agglomerations was determined and common and distinctive features of classic (urban) agglomerations and rural-urban agglomeration formations were revealed. Considerable attention is paid to the characteristics of the prerequisites and factors of the formation of rural-urban agglomerations. It has been proven that the formation within the spatial boundaries of united territorial communities and consolidated districts with a “mixed” composition of the population, available various resources and functions, common interests of the their inhabitants, united around the problem of improving the quality of life, became an impetus for the inclusion of the rural and urban population in the process creating inclusiveness. On the basis of a comparative analysis of the Ukrainian and international context of the development of rural-urban agglomeration formations on an inclusive basis, a conclusion was drawn regarding the key role of this process in restoring the peaceful life of Ukrainian communities and districts in the post-war period. This problem becomes especially relevant for the territories of Ukraine that were under occupation or suffered as a result of enemy shelling. Based on the results of the research, conclusions were drawn and the directions of further scientific research on this issue were outlined.
Keywords: інклюзивні засади, міські агломерації, реформа децентралізації, риси агломерацій, сільсько-міські агломераційні утворення, передумови та чинники формування сільсько-міських агломерацій, український та міжнародний контекст; inclusive basics, urban agglomerations, decentralization reform, features of agglomerations, rural-urban agglomeration formations, prerequisites and factors for the formation of rural-urban agglomerations, Ukrainian and international context